High sensitivity of ROSE-supported ERCP-guided brushing for biliary strictures - Archibugi, Livia; Mariani, Alberto; Ciambriello, Biagio; Petrone, Maria Chiara; Rossi, Gemma; Testoni, Sabrina Gloria Giulia; Carlucci, Michele; Aldrighetti, Luca; Falconi, Massimo; Balzano, Gianpaolo; Doglioni, Claudio; Capurso, Gabriele; Arcidiacono, Paolo Giorgio (Endoscopy International Open, 2021)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) plays a major role in biliary strictures, with brushing being a cheap and fast method to acquire a cytological specimen, despite a sensitivity around 45 %. Rapid on-site evaluation (ROSE) is widely used for endoscopic ultrasound-acquired cytological specimen adequacy, improving its sensitivity and specificity. Nevertheless, no study has evaluated its role for ERCP-guided brushing. Our aim was to assess the diagnostic yield of ERCP-guided brushing of biliary strictures when supported by ROSE.Patients and methods This was a retrospective single-center study that included patients undergoing ERCP-guided brush cytology supported by ROSE for biliary strictures. Recorded data included patient clinical-radiological and ERCP features. Final diagnosis was determined after surgery, intraductal biopsy or adequate follow-up. The diagnostic yield was calculated and a subgroup analysis for factors associated with false-negative or true-positive results was performed.Results Two hundred six patients were included, 57.3 % males, median age 72 years, 77.2 % having extrahepatic biliary strictures. Of the patients, 99 % had an adequate sample at ROSE after a mean of 2.6 passages. The diagnostic yield was accuracy 83 %, sensitivity 74.6 %, and specificity 98 %, positive and negative predictive values 98 % and 71 % respectively, with an area under the curve of 0.86. A diagnosis of cholangiocarcinoma was significantly more frequent among true-positive cases (68 % vs 46.8 %; P = 0.04).Conclusions This is the first study evaluating the use of ROSE as support for ERCP-guided brushing of biliary strictures, with a sensitivity far higher than those reported for brushing alone and at least comparable to those of more expensive and invasive techniques.